The state of cervical cancer screening in imprisoned women in Malawi: a case of Maula Prison - Regina Mendulo; Isabel Kazanga Chiumia (BMC, 2023)
Abstract Background Malawi is one of the countries with the highest burden of cervical cancer in the world with less than ten percent of women screened for cervical cancer annually. The study aimed to investigate the state of cervical cancer screening among incarcerated women at Maula prison. The study highlights key challenges that women in prison face to access cervical cancer screening to inform policies and strategies to address them. Methods The study employed a cross-sectional qualitative study design. A total of 31 prisoners aged between 18 to 49 participated in the study. Among these, 15 women participated in in-depth interviews, while 16 women participated in two focus group discussions consisting of 8 women per group. All interviews were recorded and transcribed verbatim. Data was analysed using inductive content analysis. Findings Majority of women at Maula prison demonstrated knowledge of cervical cancer, its associated risk factors and the benefits of cervical cancer screening. Most women also expressed willingness to undergo cervical cancer screening. However, the following were identified as factors that hinder women from accessing cervical cancer screening services at the prison:-limited availability of the services, pain during the screening process, the presence of male practitioners conducting screening, poor treatment by authorities and health workers and favouritism. Conclusion To improve cervical cancer screening and its uptake at Maula prison there is a need to ensure unlimited availability of the screening services which should be conducted by female health practitioners. There is also a need to include this service as part of the mandatory health screening exercise that is conducted upon entry into the prison by all prisoners. Conducting in-depth awareness and sensitization with participants before screening would help to eradicate fear, provide assurance and clarification of the screening process. Prison officers and health workers should also be sensitised to improve prisoners' access to healthcare during incarceration.